Dermatology and Diabetes (Springer International Publishing, 2018)
This book reviews the dermatological manifestations of Diabetes Mellitus, including a broad spectrum of conditions since the dysfunction of the cutaneous barrier, going through cutaneous infections in diabetics, dermatoses associated to Diabetes and manifestations related to Diabetes treatment. Moreover, the book comprises the latest concepts regarding epidemiology, classification, diagnosis and treatment of Diabetes Mellitus, insulin resistance and metabolic syndrome, including useful tools for the management of patients with diabetes. It explains why skin conditions have such a great impact on the quality of life of these patients, particularly the subset of patients with diabetic foot syndrome. Dermatology and Diabetes discusses all these dermatologic conditions and provides a roundup of the current guidelines in diabetic patients. Taking into account the critical differential diagnostic information and therapeutic options, the book is an important reference for clinical dermatologist and all health care professionals involved.